2018
DOI: 10.1186/s12884-018-1750-0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse obstetric and neonatal outcomes complicated by psychosis among pregnant women in the United States

Abstract: BackgroundAdverse obstetric and neonatal outcomes among women with psychosis, particularly affective psychosis, has rarely been studied at the population level. We aimed to assess the risk of adverse obstetric and neonatal outcomes among women with psychosis (schizophrenia, affective psychosis, and other psychoses).MethodsFrom the 2007 – 2012 National (Nationwide) Inpatient Sample, 23,507,597 delivery hospitalizations were identified. From the same hospitalization, International Classification of Diseases diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 53 publications
4
40
3
2
Order By: Relevance
“…the risk was specifically increased for cardiovascular anomalies. Such studies also found an increased rate of pregnancy complications, including fetal distress and placental abruption …”
Section: Results (Table )mentioning
confidence: 89%
See 1 more Smart Citation
“…the risk was specifically increased for cardiovascular anomalies. Such studies also found an increased rate of pregnancy complications, including fetal distress and placental abruption …”
Section: Results (Table )mentioning
confidence: 89%
“…The second limitation is the lack of homogeneity in the psychiatric diagnoses of the enrolled populations …”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia polygenic risk scores appear to mediate less than 20% of the effect of family history 229 . This is likely in part explained by the fact that particularly parental family history also reflects environmental influences, such as higher rates of birth and pregnancy complications 230,231 , growing up in an unfavorable home environment 232 , out-of-home placement 233 , elevated divorce rate, alterations in parental communication 234 , and poor school performance 235 . The sizeable impact of growing up with a parent with severe mental illness on psychological and social development has been recently reviewed 236 .…”
Section: Family Historymentioning
confidence: 99%
“…Schwerwiegende psychische Erkrankungen in der Schwangerschaft stellen einen relevanten Risikofaktor für Geburtskomplikationen dar. Nach einer aktuellen Registerstudie sind schizophrene und affektive Psychosen während der Schwangerschaft mit einer Vielzahl von mütterlichen, fetalen und neonatalen Komplikationen verbunden [ 28 ]. Neben immanent psychiatrischen Aspekten wie Suizidalität mit ggf.…”
Section: Hintergrundunclassified
“…Letztlich sind die absoluten und relativen Risiken der EKT in der Schwangerschaft nicht exakt bezifferbar, da kontrollierte Studien, die mittels identisch schwer erkrankter Vergleichspopulationen die Effekte der psychiatrischen Störung von denen der Behandlung differenzieren könnten, fehlen. Eine ohne Kausalitätsprüfung vorgenommene Angabe der Häufigkeit unerwünschter Ereignisse bei EKT in der Schwangerschaft wird diese jedoch überschätzen, da die EKT-assoziierten „adverse events“ [ 23 ] qualitativ weitgehend deckungsgleich mit den Risiken einer schwerwiegenden psychischen Erkrankung in der Schwangerschaft [ 14 , 28 ] sind (Tab. 1 ).…”
Section: Diskussionunclassified